PENGGUNAAN MEDIA AUDIO VISUAL DALAM PEMBELAJARAN IPA DAN TEMBANG MACAPAT DI SD - kusniasih, nur (KALAM CENDEKIA PGSD KEBUMEN, 2014)
ABSTRAK: PENGGUNAAN MEDIA AUDIO VISUAL DALAM PEMBELAJARAN IPA DAN TEMBANG MACAPAT DI SD. Penelitian ini bertujuan meningkatkan pembelajaran IPA dan meningkatkan motivasi serta hasil belajar Tembang Macapat di SD dengan menggunakan media audio visual. Penelitian ini menggunakan metode penelitian tindakan kelas yang dilaksanakan dalam tiga siklus terdiri dari perencanaan, pelaksanaan tindakan, observasi, dan refleksi. Subjek penelitian adalah siswa kelas III SD berjumlah 27 siswa terdiri 14 siswa laki-laki dan 13 siswa perempuan, kelas IV SD berjumlah 17 siswa terdiri 8 siswa laki-laki dan 9 siswa perempuan. Sumber data penelitian ini adalah siswa kelas III dan IV SD. Pengumpulan data menggunakan observasi, tes, dan angket. Validitas data menggunakan teknik triangulasi sumber data dan teknik. Analisis data menggunakan teknik deskriptif kualitatif dan kuantitatif. Hasil penelitian menunjukkan penggunaan media audio visual dapat meningkatkan pembelajaran IPA dan dapat meningkatkan motivasi serta hasil belajar Tembang Macapat di SD. Kata kunci: media audio visual, pembelajaran, motivasi, IPA, macapat ABSTRACT: THE USING OF AUDIO VISUAL MEDIA IN SCIENCE LEARNING AND MACAPAT SONG AT ELEMENTARY SCHOOL. The purpose of this research are improving science learning in grade students state elementary school and improving motivation with learning result macapat song in grade students state elementary school through using audio visual media. This research is in classroom action research there was conducted in three cycles, with each cycle consisted of three meeting and each meeting comparised four steep: planning, implementation of the action, observation and reflection. Subject of this research are the third grade students state elementary school, the value of that class are 27 with 14 boys and 13 girls, student of fourth class are 17 wih 8 boys and 9 girls. The source data came from students in the third class and fourth class of grade students state elementary school. The data collection techniques were observation, interviews, test, rating scale, and documentation. The validation of data by using triangulation technique which were data collection and technique. The data analysis used technique qualitative and quantitative descriptions. The results of the research are the using audio visual media can improve science learning and the motivation also result learning macapat song at elementary school. Key Words: audio visual media, learning, motivation, science, macapat